2013
DOI: 10.1189/jlb.0412182
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of the gliadin-specific, cell-mediated immune response by transamidation with microbial transglutaminase

Abstract: CD is an immune-mediated enteropathy caused by the ingestion of wheat gluten. The modification of gluten by intestinal tTGase plays a crucial role in CD pathogenesis. In this study, we observed that extensive transamidation of wheat flour with K-C2H5 by mTGase yielded spf and K-gliadins fractions. By Western blot, we found that these modifications were associated with strongly reduced immune cross-reactivity. With the use of DQ8 tg mice as a model of gluten sensitivity, we observed a dramatic reduction in IFNγ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 45 publications
3
29
0
Order By: Relevance
“…Western blot analysis with anti-native gliadin antiserum showed the complete loss of immune reactivity of K-gliadins and spf ( Fig. 2A), in agreement with previous findings [12]. On the contrary, anti-K-gliadin antibodies identified epitopes in all examined samples.…”
Section: Immune Cross-reactivity Of Different Gliadin Forms After Flosupporting
confidence: 91%
See 3 more Smart Citations
“…Western blot analysis with anti-native gliadin antiserum showed the complete loss of immune reactivity of K-gliadins and spf ( Fig. 2A), in agreement with previous findings [12]. On the contrary, anti-K-gliadin antibodies identified epitopes in all examined samples.…”
Section: Immune Cross-reactivity Of Different Gliadin Forms After Flosupporting
confidence: 91%
“…The production of isopeptide bonds by means of the catalytic activity of mTGase dramatically decreased the gliadin yield in wheat flour to 17.4 ± 0.7% (mean ± SD; Table 1), in agreement with previous results [12]. Interestingly, glutenins were also partially recovered following transamidation treatment (47.4 ± 2.5%, Table 1).…”
Section: Differential Solubilization Of Gluten Components Following Tsupporting
confidence: 90%
See 2 more Smart Citations
“…In silico analysis of a prototypic dominant gliadin peptide, p56-68, suggested that this occurs because binding of the cognate transamidated gliadin peptide to the DQ2 molecule is strongly reduced, even if it is not completely abolished [45]. Furthermore, in DQ8 transgenic mice, the enzymatic modification of whole gliadin was associated with an alteration of the gliadin-inducible IL-10/IFN-γ ratio, indicative of reversal of the phenotype from inflammatory to anti-inflammatory [46]. Therefore, we speculated that the transamidation of dominant peptides might favor HLA binding of low-affinity, subdominant or cryptic, gliadin determinants with dramatic consequences for the immune outcome.…”
Section: Induction Of Gluten Tolerance By Antigen Manipulationmentioning
confidence: 99%